Myxobacteria and their products: current trends and future perspectives in industrial applications - Shrivastava, Akansha; Sharma, Rakesh Kumar (Folia microbiologica, 2021)
Myxobacteria belong to a group of bacteria that are known for their well-developed communication system and synchronized or coordinated movement. This typical behavior of myxobacteria is mediated through secondary metabolites. They are capable of producing secondary metabolites belonging to several chemical classes with unique and wide spectrum of bioactivities. It is predominantly significant that myxobacteria specialize in mechanisms of action that are very rare with other producers. Most of the metabolites have been explored for their medical and pharmaceutical values while a lot of them are still unexplored. This review is an attempt to understand the role of potential metabolites produced by myxobacteria in different applications. Different myxobacterial metabolites have demonstrated antibacterial, antifungal, and antiviral properties along with cytotoxic activity against various cell lines. Beside their metabolites, these myxobacteria have also been discussed for better exploitation and implementation in different industrial sectors.
Keywords: Myxococcales; antibakteriální látky; průmyslová mikrobiologie; Industrial Microbiology; Anti-Bacterial Agents